Persulfate activation induced by ascorbic acid for efficient organic pollutants oxidation - Hou, Xiaojing; Zhan, Guangming; Huang, Xiaopeng; Wang, Nan; Ai, Zhihui; Zhang, Lizhi (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •Ascorbic acid exhibited extremely high activity on persulfate activation to produce SO4− and OH.•Atrazine degradation rate constant during PS activation in presence of AA was 29 times that in absence of AA.•Atrazine, pentachlorophenol, alachlor, tetracycline, and chloramphenicol were effectively degraded by AA/PS.•Persulfate activation by ascorbic acid was attributed to the electron transfer from AA to PS.•Atrazine in the real aquifer sediment system could be totally oxidized by AA/PS process. In this study, we demonstrate that ascorbic acid (AA) exhibited extremely high activity on persulfate (PS) activation (AA/PS) to produce SO4− and OH for the degradation of various organic pollutants, including atrazine, pentachlorophenol, alachlor, tetracycline, and chloramphenicol. Taken atrazine as a model natural organic micropollutants, we surprisingly found that the degradation rate constant of atrazine during PS activation in presence of AA was about 29 times larger than that in the absence of AA. The underlying mechanism of persulfate activation induced by AA was then systematically investigated by electron spin resonance (ESR) analysis, theoretical density functional theory (DFT) calculations, and kinetic experiments. The combination of ESR and DFT results confirmed that the persulfate activation induced by ascorbic acid was attributed to the electron transfer from AA to PS. In this process, AA undergoes a two-step oxidation by PS to generate SO4− and dehydroascorbic acid with the formation of an intermediate ascorbate free radical. More interestingly, atrazine in the real aquifer sediment system could be totally oxidized in the presence of PS and AA. These findings offer a new economically feasible persulfate activation strategy for the in situ chemical oxidation of organic compounds in contaminated water and sediment systems.